Xerophilic Moulds Isolated from Salted and Unsalted Dried Fish from Traditional Markets in Jakarta - I. Santoso; I. Gandjar; R. D. Sari; N. D. Sembiring (Indonesian Association of Food Technologists, 1999)
A study was carried out on the mycoflora of utz salted (30 samples) and salted (30 samples) dried fish sold at traditional markets in Jakarta and vicinity. Only the moulds growing directly on the surface on the fish were isolated. The isolates were identified until the species level using the common suitable recommended media. For examination of their xerophilic features DG18% Agar was used. The species isolated from both kind of samples belong to the genera Absidia, Aspergillus, Chaetomium, Cladosporium, Doratomuces, Fusarium, Moniliella, Mucor, Neurospora/Chrysonilia, Nigrospora, Rhizopus, Sordaria, and Syncephalastrum. The strong xerophilic isolates belong to the species Aspergillus awainori, Asp. carbonarius, Asp. glaucus, Asp. tamarii, and Eurotium glaucus.